Roles of Pyroptosis-Related Gene Signature in Prediction of Endometrial Cancer Outcomes - Chen, Yili; Liao, Yuandong; Du, Qiqiao; Shang, Chunliang; Qin, Shuhang; Lee, Kaping; Zou, Qiaojian; Liu, Junxiu; Yao, Shuzhong (Frontiers in Medicine, 2022)
Endometrial cancer (EC) is one of the most common gynecological malignancies in women, accompanied by the increasing incidence and decreasing age of onset. Pyroptosis plays an important role in the occurrence and development of malignant tumors. However, the relationship between pyroptosis-related genes and tumor prognosis remains unclear. In this study, analyzing the expression levels and survival data of 33 pyroptosis-related genes in the Cancer Genome Atlas (TCGA) between normal samples and tumor samples, we obtained six pyroptosis-related prognostic differentially expressed genes (DEGs). Then, through the least absolute shrinkage and selection operator (LASSO) regression analysis, a gene signature composed of six genes (GPX4, GSDMD, GSDME, IL6, NOD2 and PYCARD) was constructed and divided patients into high- and low-risk groups. Subsequently, Kaplan-Meier (KM) plot, receiver operating characteristic (ROC) curve and principal component analysis (PCA) in two cohorts demonstrated that the gene signature was an efficient independent prognostic indicator. The enrichment analysis and immune infiltration analysis indicated that the high-risk group generally has lower immune infiltrating cells and less active immune function. In short, we constructed and validated a pyroptosis-related gene signature to predict the prognosis of EC, which is correlated to immune infiltration and proposed to help the precise diagnosis and therapy of EC.